Requirement of LIM domains for the transient accumulation of paxillin at damaged stress fibres - Watanabe-Nakayama, Takahiro (The Company of Biologists, 2013)
Cells recognize and respond to changes in intra- and extracellular mechanical conditions to maintain their mechanical homeostasis. Linear contractile bundles of actin filaments and myosin II known as stress fibres (SFs) mediate mechanical signals. Mechanical cues such as excessive stress driven by myosin II and/or external force may damage SFs and induce the local transient accumulation of SF-repair complexes (zyxin and VASP) at the damaged sites. Using an atomic force microscope mounted on a fluorescence microscope, we applied mechanical damage to cells expressing fluorescently tagged cytoskeletal proteins and recorded the subsequent mobilization of SF-repair complexes. We found that a LIM protein, paxillin, transiently accumulated at the damaged sites earlier than zyxin, while paxillin knockdown did not affect the kinetics of zyxin translocation. The C-terminal half of paxillin, comprising four-tandem LIM domains, can still translocate to damaged sites on SFs, suggesting that the LIM domain is essential for the mechanosensory function of paxillin. Our findings demonstrate a crucial role of the LIM domain in mechanosensing LIM proteins.